Molded steel liquid covering agent and preparation process thereof

By using porous calcium zirconate and acidified graphite as the main components, combined with sintering and stirring processes, the problem of insufficient insulation and oxidation resistance of existing cover agents in casting of low carbon steel and ultra-low carbon steel is solved, and higher thermal insulation and anti-oxidation effects are achieved.

CN119634689APending Publication Date: 2025-03-18XIXIA COUNTY CHENGRUN METALLURGICAL MATERIALS CO LTD

Patent Information

Application Number
CN202411714904.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing cover agents are insufficient in thermal insulation and oxidation resistance in low carbon steel and ultra-low carbon steel casting, and cannot effectively reduce the carbon content to meet the needs of low carbon steel.

Method used

Using porous calcium zirconate and acidified graphite as main components, porous calcium zirconate and acidified graphite are prepared and mixed with other oxide powders to form a covering agent. The process includes sintering and crushing of porous calcium zirconate, preparation of acidified graphite, and mixing and stirring of components.

Benefits of technology

It significantly improves the thermal insulation and antioxidant ability of the cover agent, and is suitable for casting of low-carbon steel and ultra-low-carbon steel, reduces the content of carbon elements, avoids liquid steel oxidation, and increases the cooling rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156678140000081
    Figure BDA0005156678140000081
Patent Text Reader

Abstract

The invention discloses a mold casting molten steel covering agent and a preparation method thereof, and the mold casting molten steel covering agent comprises the following components in parts by mass: 50-65 parts of expanded perlite, 6-10 parts of alumina powder, 2-5 parts of magnesium oxide powder, 25-35 parts of calcium oxide powder, 1-2 parts of fluorite powder, 2-5 parts of ferric oxide, 30-40 parts of porous calcium zirconate, 5-10 parts of calcium carbonate powder and 3-5 parts of acidified graphite. According to the invention, the proportion of carbon element and hydrous aluminosilicate in the covering agent is reduced, the recarburization effect on molten steel is reduced, and the oxidation resistance and thermal insulation capacity of the covering agent are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of covering agents, in particular to a mold casting molten steel covering agent and a preparation process thereof. Background Art

[0002] Due to the need for the development of continuous casting technology, the residence time of molten steel in the ladle will be extended. In order to meet the requirements of subsequent processes, thermal insulation covering agents must be added to the molten steel after steelmaking is completed. The role of thermal insulation covering agents is very important because they can prevent secondary oxidation of molten steel in the ladle, reduce the cooling of molten steel, provide molten steel with suitable temperature for continuous casting, and ensure the smooth pouring of subsequent work sections.

[0003] Traditional covering agents mostly use rice husk carbon, which is widely available and inexpensive, and has long occupied an important position in the field of covering agents. Patent 202311794555.3 discloses a riser covering agent and its preparation method, which is made by mixing and stirring plant ash, sawdust, acid graphite and perlite in a certain ratio. However, the carbon element in the covering agent accounts for too much proportion, and it is easy to increase carbon content of low-carbon steel and ultra-low-carbon steel when in contact with molten steel. At the same time, it has a high carbon content and strong conductivity, which can easily cause a short circuit in the driving cable.

[0004] Patent 201310529378.6 discloses a thermal insulation covering agent and a preparation method thereof, which is made by granulating components such as SiO2, Al2O3, CaO, Fe2O3, C, MgO, an expansion agent, and a heating agent. The final product is a granular material. The gaps between the granules are large, and air and heat are easily conducted through them, and a stable thermal insulation layer cannot be effectively formed, and the anti-oxidation and thermal insulation effects are poor.

[0005] How to reduce the carbon content of the covering agent to meet the casting needs of low-carbon steel and ultra-low-carbon steel, while ensuring that the covering agent continues to maintain high thermal insulation and antioxidant capabilities is a difficult point in corporate research and development. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a casting molten steel covering agent and a preparation process thereof to solve the problem that the existing covering agent has weak thermal insulation and oxidation resistance and is not applicable to low carbon steel and ultra-low carbon steel.

[0007] The purpose of the present invention is achieved by the following technical scheme: a mold casting molten steel covering agent, which includes the following components by mass: 50-65 parts of expanded perlite, 6-10 parts of alumina powder, 2-5 parts of magnesium oxide powder, 25-35 parts of calcium oxide powder, 1-2 parts of fluorite powder, 2-5 parts of ferric oxide, 30-40 parts of porous calcium zirconate, 5-10 parts of calcium carbonate powder, and 3-5 parts of acidified graphite.

[0008] Preferably, the particle size of the expanded perlite and the fluorite powder is less than 3 mm.

[0009] Preferably, the porous calcium zirconate is prepared according to the following method:

[0010] S1. Calcium carbonate powder, zirconium oxide powder, calcium chloride powder, and pure calcium aluminate cement are weighed in a mass ratio of 12:13:14:2;

[0011] S2. Add water, mix well and pour into a mold to solidify;

[0012] S3. The solidified block is placed in a furnace and sintered at 900°C for 3.5h;

[0013] S4. The sintered solid block is crushed to obtain porous calcium zirconate.

[0014] Preferably, in step S1, polyurethane short fibers are also included, and the length of the polyurethane short fibers is 2 mm.

[0015] Preferably, the mass ratio of the calcium carbonate powder, zirconium oxide powder, calcium chloride powder, pure calcium aluminate cement, and polyurethane short fiber is 12:13:14:2:1.

[0016] Preferably, the particle size of the porous calcium zirconate is 3-5 mm.

[0017] Preferably, the acidified graphite is prepared according to the following method: graphite and potassium permanganate are put into a concentrated sulfuric acid solution to react for 10 minutes, and then taken out, washed with pure water and dried.

[0018] The second object of the present invention is to provide a process for preparing a casting steel liquid covering agent, which is characterized in that the process is prepared according to the following steps:

[0019] S1. The porous calcium zirconate and calcium carbonate powders were put into a drum mixer and stirred for 1h;

[0020] S2. Put the remaining components, expanded perlite, alumina powder, magnesium oxide powder, calcium oxide powder, fluorite powder, ferric oxide, and acidified graphite into a mixer and stir for 0.5h.

[0021] Preferably, in step S1, vermiculite is ground into powder and put into a sodium silicate solution and stirred to mix evenly, porous calcium zirconate is filtered from calcium carbonate powder using a sieve, the separated porous calcium zirconate is immersed in sodium silicate, and the immersed porous calcium zirconate is dried at a temperature of 100-120°C.

[0022] The present invention has the following advantages:

[0023] 1. By using a large amount of porous calcium zirconate in the covering agent, the use of hydrated aluminosilicates such as vermiculite and expanded perlite is reduced, which avoids the problem of rapid temperature drop caused by the dehydration and heat absorption of hydrated aluminosilicates under high temperature and rapid overflow. Its porous structure not only reduces the density, but also effectively prevents rapid heat exchange;

[0024] 2. The organic fiber added in the preparation process of porous calcium zirconate can be ablated under the influence of high temperature and form a large channel that is conducive to the entry and exit of powder. After calcium carbonate enters the cavities of porous calcium zirconate through the large pores, a plugging material formed by a mixture of sodium silicate and vermiculite is used to plug the holes on the surface of the cavities, so that calcium carbonate is thermally decomposed under the influence of high temperature to form a large amount of carbon dioxide to fill the cavities formed by porous calcium zirconate. Since carbon dioxide gas has stronger heat insulation and heat preservation capabilities than other gases, the independent air cavities formed by a large amount of carbon dioxide gather to form a "quilt" covering the molten steel, which can effectively reduce heat dissipation. At the same time, a small amount of carbon dioxide overflowing from the cavities reacts with acidified graphite to generate carbon monoxide. Carbon monoxide, as a gas reducing agent, has a stronger effect than the gap formed by multiple components of solid graphite filling covering agent, which can effectively prevent oxidation of molten steel;

[0025] 3. Replacing the rice husk carbon used in the existing covering agent with acidified graphite can not only significantly reduce the carbon content in the covering agent and reduce the impact on the carbon content of the molten steel in the ladle, but also the acidified graphite will expand several times after high-temperature firing. In combination with expanded perlite, it can push other powder particles and porous calcium zirconate to form a dense structure during the expansion process, effectively preventing gas and heat from being exchanged inside and outside, and further improving the anti-oxidation and heat preservation capabilities of the covering agent. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described below.

[0027] Example 1

[0028] A casting steel liquid covering agent is prepared according to the following steps:

[0029] S1. Preparation of porous calcium zirconate: Calcium carbonate powder, zirconium oxide powder, calcium chloride powder, and pure calcium aluminate cement were weighed in a mass ratio of 12:13:14:2, and the weighed components were put into a mixing bucket, water, and a water reducer were added, and mixed for 1 hour. After stirring evenly, the mixture was poured into a square mold and naturally solidified into a block. The solidified block was placed in a furnace and sintered at 900°C for 3.5 hours. The sintered solid block was taken out of the furnace and crushed in a crusher, and the porous calcium zirconate with a particle size of 3-5 mm was separated by sieving;

[0030] S2. Preparation of acidified graphite: According to the mass ratio of natural flake graphite, potassium permanganate, 95% concentrated sulfuric acid 1:0.2:3, graphite and potassium permanganate were put into concentrated sulfuric acid solution and stirred for 10 min, then washed with pure water until neutral, and dried at 60 ° C;

[0031] S3 filled with calcium carbonate powder: 40 parts of porous calcium zirconate and 10 parts of calcium carbonate powder were added to a drum mixer and stirred for 1h to allow the calcium carbonate powder to enter the cavities of the porous calcium zirconate;

[0032] S4. Mixing: according to the mass ratio, weigh 65 parts of expanded perlite, 10 parts of alumina powder, 5 parts of magnesium oxide powder, 25 parts of calcium oxide powder, 2 parts of fluorite powder, 2 parts of ferric oxide, and 5 parts of acidified graphite, put them into a drum mixer and stir for 0.5h, wherein the expanded perlite and fluorite powder are sieved through a 5-mesh sieve.

[0033] Example 2

[0034] A casting steel liquid covering agent, which differs from Example 1 in that in step S1, the other steps are the same, calcium carbonate powder, zirconium oxide powder, calcium chloride powder, pure calcium aluminate cement, and 2mm polyurethane short fiber are weighed according to a mass ratio of 12:13:14:2:1, the weighed components are put into a mixing bucket, water and a water reducer are added, and the mixture is stirred for 1 hour, after stirring evenly, the mixture is poured into a square mold and naturally solidified into a block, the solidified block is put into a furnace and sintered at 900°C for 3.5 hours, the sintered solid block is taken out of the furnace and put into a crusher for crushing, and porous calcium zirconate with a particle size of 3-5 mm is separated by sieving.

[0035] Example 3

[0036] A casting steel liquid covering agent is prepared according to the following steps:

[0037] S1. Preparation of porous calcium zirconate: calcium carbonate powder, zirconium oxide powder, calcium chloride powder, pure calcium aluminate cement, and 2 mm polyurethane short fibers were weighed in a mass ratio of 12:13:14:2:1, and the weighed components were put into a mixing bucket, water and a water reducer were added, and the mixture was stirred for 1 hour. After stirring evenly, the mixture was poured into a square mold and naturally solidified into a block. The solidified block was placed in a furnace and sintered at 900 ° C for 3.5 hours. The sintered solid block was taken out of the furnace and crushed in a crusher, and the porous calcium zirconate with a particle size of 3-5 mm was separated by sieving;

[0038] S2. Preparation of acidified graphite: According to the mass ratio of natural flake graphite, potassium permanganate, 95% concentrated sulfuric acid 1:0.2:3, graphite and potassium permanganate were put into concentrated sulfuric acid solution and stirred for 10 min, then washed with pure water until neutral, and dried at 60 ° C;

[0039] S3 filled with calcium carbonate powder: 30 parts of porous calcium zirconate and 5 parts of calcium carbonate powder were added to a drum mixer and stirred for 1h to allow the calcium carbonate powder to enter the cavities of the porous calcium zirconate;

[0040] S4. Blocking: The vermiculite was put into a ball mill and ground into powder, passed through a 500 mesh sieve, and mixed with 35% sodium silicate solution in a volume ratio of 1:8, and the porous calcium zirconate was filtered from the calcium carbonate powder using a sieve, and the separated porous calcium zirconate was immersed in the sodium silicate solution for several times, each time for 10 minutes, and the porous calcium zirconate after immersion was filtered and dried at a temperature of 100-120 ° C;

[0041] S5. Mixing: according to the mass ratio, weigh 65 parts of expanded perlite, 10 parts of alumina powder, 5 parts of magnesium oxide powder, 25 parts of calcium oxide powder, 2 parts of fluorite powder, 2 parts of ferric oxide, and 5 parts of acidified graphite, put them into a drum mixer and stir for 0.5h. The expanded perlite and fluorite powder are sieved through a 5-mesh sieve.

[0042] Example 4

[0043] A casting steel liquid covering agent is prepared according to the following steps:

[0044] S1. Preparation of porous calcium zirconate: calcium carbonate powder, zirconium oxide powder, calcium chloride powder, pure calcium aluminate cement, and 2 mm polyurethane short fibers were weighed in a mass ratio of 12:13:14:2:1, and the weighed components were put into a mixing bucket, water and a water reducer were added, and the mixture was stirred for 1 hour. After stirring evenly, the mixture was poured into a square mold and naturally solidified into a block. The solidified block was placed in a furnace and sintered at 900 ° C for 3.5 hours. The sintered solid block was taken out of the furnace and crushed in a crusher, and the porous calcium zirconate with a particle size of 3-5 mm was separated by sieving;

[0045] S2. Preparation of acidified graphite: According to the mass ratio of natural flake graphite, potassium permanganate, 95% concentrated sulfuric acid 1:0.2:3, graphite and potassium permanganate were put into concentrated sulfuric acid solution and stirred for 10 min, then washed with pure water until neutral, and dried at 60 ° C;

[0046] S3 filled with calcium carbonate powder: 40 parts of porous calcium zirconate and 10 parts of calcium carbonate powder were added to a drum mixer and stirred for 1h to allow the calcium carbonate powder to enter the cavities of the porous calcium zirconate;

[0047] S4. Blocking: The vermiculite was put into a ball mill and ground into powder, passed through a 500 mesh sieve, and mixed with 35% sodium silicate solution in a volume ratio of 1:8, and the porous calcium zirconate was filtered from the calcium carbonate powder using a sieve, and the separated porous calcium zirconate was immersed in the sodium silicate solution for several times, each time for 10 minutes, and the porous calcium zirconate after immersion was filtered and dried at a temperature of 100-120 ° C;

[0048] S5. Mixing: according to the mass ratio, weigh 50 parts of expanded perlite, 6 parts of alumina powder, 2 parts of magnesium oxide powder, 35 parts of calcium oxide powder, 1 part of fluorite powder, 5 parts of ferric oxide and 3 parts of acidified graphite, put them into a drum mixer and stir for 0.5h. The expanded perlite and fluorite powder are sieved through a 5-mesh sieve.

[0049] Comparative Example 1

[0050] A casting steel liquid covering agent is prepared according to the following steps:

[0051] S1. Preparation of porous calcium zirconate: Calcium carbonate powder, zirconium oxide powder, calcium chloride powder, and pure calcium aluminate cement were weighed in a mass ratio of 12:13:14:2, and the weighed components were put into a mixing bucket, water, and a water reducer were added, and mixed for 1 hour. After stirring evenly, the mixture was poured into a square mold and naturally solidified into a block. The solidified block was placed in a furnace and sintered at 900°C for 3.5 hours. The sintered solid block was taken out of the furnace and crushed in a crusher, and the porous calcium zirconate with a particle size of 3-5 mm was separated by sieving;

[0052] S2. Preparation of acidified graphite: According to the mass ratio of natural flake graphite, potassium permanganate, 95% concentrated sulfuric acid 1:0.2:3, graphite and potassium permanganate were put into concentrated sulfuric acid solution and stirred for 10 min, then washed with pure water until neutral, and dried at 60 ° C;

[0053] S3. Mixing: according to the mass ratio, weigh 65 parts of expanded perlite, 10 parts of alumina powder, 5 parts of magnesium oxide powder, 25 parts of calcium oxide powder, 2 parts of fluorite powder, 2 parts of ferric oxide, 40 parts of porous calcium zirconate, 10 parts of calcium carbonate powder and 5 parts of acidified graphite, put them into a drum mixer and stir for 0.5h. The expanded perlite and fluorite powder are sieved through a 5-mesh sieve.

[0054] Comparative Example 2

[0055] A casting steel liquid covering agent is prepared according to the following steps:

[0056] S1. Preparation of porous calcium zirconate: calcium carbonate powder, zirconium oxide powder, calcium chloride powder, pure calcium aluminate cement, and 2 mm polyurethane short fibers were weighed in a mass ratio of 12:13:14:2:1, and the weighed components were put into a mixing bucket, water and a water reducer were added, and the mixture was stirred for 1 hour. After stirring evenly, the mixture was poured into a square mold and naturally solidified into a block. The solidified block was placed in a furnace and sintered at 900 ° C for 3.5 hours. The sintered solid block was taken out of the furnace and crushed in a crusher, and the porous calcium zirconate with a particle size of 3-5 mm was separated by sieving;

[0057] S2. Preparation of acidified graphite: According to the mass ratio of natural flake graphite, potassium permanganate, 95% concentrated sulfuric acid 1:0.2:3, graphite and potassium permanganate were put into concentrated sulfuric acid solution and stirred for 10 min, then washed with pure water until neutral, and dried at 60 ° C;

[0058] S3 filled with calcium carbonate powder: 30 parts of porous calcium zirconate and 5 parts of calcium carbonate powder were added to a drum mixer and stirred for 1h to allow the calcium carbonate powder to enter the cavities of the porous calcium zirconate;

[0059] S4. Plugging: The porous calcium zirconate is filtered from the calcium carbonate powder using a sieve, and the separated porous calcium zirconate is immersed in a 35% sodium silicate solution for multiple times, each time for 10 minutes, and the porous calcium zirconate after immersion is filtered and dried at a temperature of 100-120°C;

[0060] S5. Mixing: according to the mass ratio, weigh 65 parts of expanded perlite, 10 parts of alumina powder, 5 parts of magnesium oxide powder, 25 parts of calcium oxide powder, 2 parts of fluorite powder, 2 parts of ferric oxide, and 5 parts of acidified graphite, put them into a drum mixer and stir for 0.5h. The expanded perlite and fluorite powder are sieved through a 5-mesh sieve.

[0061] Comparative Example 3

[0062] A mold casting molten steel covering agent is prepared according to the following steps, and each component is weighed and mixed evenly according to the following mass parts: 65 parts of expanded perlite, 10 parts of aluminum oxide powder, 5 parts of magnesium oxide powder, 25 parts of calcium oxide powder, 2 parts of fluorite powder, 2 parts of ferric oxide, 50 parts of rice husk carbon, and 5 parts of vermiculite.

[0063] The covering agents prepared in Examples 1-4 and Comparative Examples 1-2 were applied in a continuous casting process and the effects were tested. The results are as follows:

[0064]

[0065] It can be seen from the above table that the covering agent prepared by the present invention has less carbon addition on medium carbon steel. Compared with the covering agent with rice husk carbon as the main component, it has no flame, smoke and does not pollute the surrounding environment. Compared with the rice husk carbon covering agent, it can reduce the cooling rate by 1.1°C / min, has good thermal insulation effect, and can meet the requirements of the continuous casting process.

[0066] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A casting steel liquid covering agent, characterized in that: The composition includes the following components by weight: 50-65 parts of expanded perlite, 6-10 parts of alumina powder, 2-5 parts of magnesium oxide powder, 25-35 parts of calcium oxide powder, 1-2 parts of fluorite powder, 2-5 parts of ferric oxide, 30-40 parts of porous calcium zirconate, 5-10 parts of calcium carbonate powder and 3-5 parts of acidified graphite.

2. A casting steel liquid covering agent according to claim 1, characterized in that: The particle sizes of the expanded perlite and the fluorite powder are less than 3 mm.

3. A casting steel liquid covering agent according to claim 1, characterized in that: The porous calcium zirconate is prepared according to the following method: S1. Calcium carbonate powder, zirconium oxide powder, calcium chloride powder, and pure calcium aluminate cement are weighed in a mass ratio of 12:13:14:2; S2. Add water, mix well and pour into a mold to solidify; S3. The solidified block is placed in a furnace and sintered at 900°C for 3.5h; S4. The sintered solid block is crushed to obtain porous calcium zirconate.

4. A casting steel liquid covering agent according to claim 3, characterized in that: In step S1, short polyurethane fibers are also included, and the length of the short polyurethane fibers is 2 mm.

5. A casting steel liquid covering agent according to claim 4, characterized in that: The mass ratio of the calcium carbonate powder, zirconium oxide powder, calcium chloride powder, pure calcium aluminate cement and polyurethane short fiber is 12:13:14:2:

1.

6. A casting steel liquid covering agent according to claim 1 or 3, characterized in that: The particle size of the porous calcium zirconate is 3-5 mm.

7. A casting steel liquid covering agent according to claim 1, characterized in that: The acidified graphite is prepared according to the following method: graphite and potassium permanganate are put into a concentrated sulfuric acid solution to react for 10 minutes, and then taken out, washed with pure water and dried.

8. A process for preparing a casting steel liquid covering agent according to any one of claims 1 to 7, characterized in that: Prepare according to the following steps, S1. The porous calcium zirconate and calcium carbonate powders were put into a drum mixer and stirred for 1h; S2. Add the remaining components, including expanded perlite, alumina powder, magnesium oxide powder, calcium oxide powder, fluorite powder, ferric oxide and acidified graphite, into a blender and stir for 0.5 h.

9. The process for preparing a casting steel liquid covering agent according to claim 8, characterized in that: In step S1, vermiculite is ground into powder and put into sodium silicate solution to stir and mix evenly, porous calcium zirconate is filtered from calcium carbonate powder using a sieve, the separated porous calcium zirconate is immersed in sodium silicate, and the immersed porous calcium zirconate is dried at a temperature of 100-120°C.

Citation Information

Patent Citations

  • Thermal-insulation cover agent and preparation method thereof

    CN103586426A

  • Riser covering agent and preparation method thereof

    CN117753953A

Cited By

  • In-situ foaming feeding agent for die casting steel ingot and preparation method of in-situ foaming feeding agent

    CN121535144A